2024
DOI: 10.1002/ldr.5022
|View full text |Cite
|
Sign up to set email alerts
|

Guiding and constraining reclamation for coastal zone through identification of response thresholds for ecosystem services supply–demand relationships

Chenghao Liu,
Xiaolu Yan,
Zenglin Han
et al.

Abstract: Enhancing the understanding and management of ecosystem services (ESs) supply and demand under the influence of global change is crucial for sustaining human well‐being and promoting sustainable development. However, the comprehension of changes in ecosystem service dynamics in the face of complex human disturbances remains limited. This study focuses on four representative ESs in the northern Liaodong Bay, a typical global estuary wetland, to elucidate alterations in the supply and demand of these ESs and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Many studies have shown that the random forest model is a machine learning algorithm based on statistics that can quantify the relative importance of driving factors and their nonlinear relationships, revealing their threshold effects and effectively compensating for the shortcomings of traditional methods [16,28]. The random forest model performs well in identifying the driving mechanisms of specific ESs, but research on the driving mechanisms of the supply and demand bal-ance of multiple ESs and the threshold effects needs to be strengthened [43]. Few studies have focused on the nonlinear response processes of multiple ES supply, demand, and supply-demand balance mechanisms to dominant factors when considering the mechanisms driving ESs [9,28,44].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the random forest model is a machine learning algorithm based on statistics that can quantify the relative importance of driving factors and their nonlinear relationships, revealing their threshold effects and effectively compensating for the shortcomings of traditional methods [16,28]. The random forest model performs well in identifying the driving mechanisms of specific ESs, but research on the driving mechanisms of the supply and demand bal-ance of multiple ESs and the threshold effects needs to be strengthened [43]. Few studies have focused on the nonlinear response processes of multiple ES supply, demand, and supply-demand balance mechanisms to dominant factors when considering the mechanisms driving ESs [9,28,44].…”
Section: Introductionmentioning
confidence: 99%